Self-loosening behavior of bolt in curvic coupling due to materials ratcheting at thread root. (May 2019) - Jiang, Xiangjun; Li, Zhi; Wang, Yanping; Pan, Fengqun
This article presents the bolt self-loosening mechanism in curvic coupling due to the structural ratcheting under cyclic loading. Finite element simulations are carried out under several loading conditions with different preloads and cyclic torque loadings on curvic coupling. To avoid relative rotation between bolt and nut in simulation, the surface between the threads of bolt and nut are connected together. The finite element analysis results reveal that the local cyclic plasticity occurring near the roots of the engaged threads resulted in cyclic strain ratcheting. The structural ratcheting causes the gradual loss of clamping force with loading cycles in bolts and the stresses to redistribute in the curvic coupling. Either the structural ratcheting behavior or the fatigue strength of the curvic coupling is more sensitive to the magnitude of the torque load in contrast to the magnitude of the preload of the bolt. Comparatively, the large preload of the bolt or the low magnitude of the torque load is benefit for improving the structural integrity in curvic coupling under the bolt self-loosening.